An improved high-resolution method for quantitative separation of empty and filled AAV8 capsids by strong anion exchange HPLC - Schrecke, Samantha; McManus, Kevin; Moshfegh, Cassandra; Stone, Jessica; Nguyen, Thuy-Uyen; Rivas, Gustavo; Muhamed, Ismaeel; Mitchell, Daniel A. J. (Frontiers in Bioengineering and Biotechnology, 2024)
Cell and Gene Therapy (CGT) is a field of therapeutic medicines that aim to treat, prevent and cure diseases using engineered cells (stem cells, immune cells, differentiated adult or fetal cells), vectors (AAV, AV, HSV, BV, LV, RV etc) and other carriers (non-viral vectors, VLP, LNP, etc.). Among viral CGT vectors Adeno-Associated Viruses and Lentiviruses (AAV and LV) are the most widely applied vector platform. The presence of non-functional vectors (empty or non-infectious vectors that carry null or partial genes) in the final drug product is classified as an impurity by the FDA. These impurities impair dosage accuracy, induce non-specific immunogenicity, and variability in drug efficacy. These non-functional viral vectors in the drug product need to be elucidated following ICH guidelines for clinical manufacturing of the final drug product. This article showcases an IEX high resolution method supporting ICH guidelines using commercially available AAV8 filled and empty capsids as reference standards. Our method successfully separated empty to full capsids with a resolution of 15 and sustained a linearity greater than 0.98 under a wide range of empty or full viral particle concentrations (E+9 to E+13 vp/mL), which is an upgrade to other IEX capsid separation methods. The medium throughput capacity and shorter sample processing time improves testing efficiency and saves cost while delivering quality as value. The discussed method is a reliable and reproducible platform to precisely evaluate the presence of non-functional viral particles in AAV8 samples. Aligned with other orthogonal results, the method is a powerful tool to improve the quality of rAAV analytics.